Maluliyet Kalıcı Bedensel Hasarların Değerlendirilmesi - Çetin, Ebubekir; Dokgöz, Halis; Can, İsmail Özgür and Savaş, Çağdaş and Ünaldı, Şeyma Tuğçe and Kalemci, Orhan and Poyraz, Turan and Ergönen, Akça Toprak and Aydoğdu, Halil İlhan and Akpınar, Ramazan and Kurt, Ceren Görkem and Kaya, Kenan and Özesen, Toygün Anıl and Kokaçya, Ömer and Tutam, Duygu Nur and Geniş, Bahadır and Çolak, Başar and Yuluğ, Emre and Bıkmazer, Alperen and Turan, Abdullah and Yıldırım, Hümeyra and Orhan, Kadir Serkan and Biçen, Emin and Yıldız, Abdulkadir and Fidancı, Sümeyye and Gürpınar, Süleyman Serhat and Karabağ, Gökmen and Zeybek, Volkan and Tuncel, Elif Tuğba and Yavuz, Mehmet Sunay and Koca Yavuz, Tuğçe and Mirioğlu, Akif and Eroğlu, İbrahim and Malkoç, Mehmet Ali and Güner, Mehri and Seviçin, Sedat and Arıcan, Nadir and Can, Muhammet and Nurdoğan, Kübra and Bütün, Celal and Yaşat Aksay, Ebru and Ten, Barış and Apaydın, Feramuz Demir and Bilgin, Tuğsan Egemen and Metin, Ali and Selek Çırakoğlu, Selin and Çırakoğlu, Emre and Çekiç, Sezer and Beşkoç, Caner and Aktürk, Gökhan and Cavlak, Mehmet and Akçan, Ramazan and Balseven Odabaşı, Aysun and Tümer, Ali Rıza and Baransel Isır, Aysun and Eröz, Halid and Akbaba, Murat and Serap Aytuğ, Şahnur and Kar, Hakan and Aktaş, Ekin Özgür and Yıldız, Ceren and Aydın, Berna and Çolak, Başar and Kar, Hakan (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-